On a sub–supersolution method for variational inequalities with Leray–Lions operators in variable exponent spaces - Le, Vy Khoi (Nonlinear analysis, 2009)
In this paper, we consider a sub–supersolution method for variational inequalities with Leray–Lions operators in Sobolev spaces with variable exponents. Existence and qualitative properties of solutions between sub and supersolutions are established.